Flow Cytometry Based Detection and Isolation of Plasmodium falciparum Liver Stages In Vitro - Dumoulin, Peter C.; Trop, Stefanie A.; Ma, Jinxia; Zhang, Hao; Sherman, Matthew A.; Levitskaya, Jelena (PLOS ONE, 2015)
Malaria, the disease caused by Plasmodium parasites, remains a major global health burden. The liver stage of Plasmodium falciparum infection is a leading target for immunological and pharmacological interventions. Therefore, novel approaches providing specific detection and isolation of live P. falciparum exoerythrocytic forms (EEFs) are warranted. Utilizing a recently generated parasite strain expressing green fluorescent protein (GFP) we established a method which, allows for detection and isolation of developing live P. falciparum liver stages by flow cytometry. Using this technique we compared the susceptibility of five immortalized human hepatocyte cell lines and primary hepatocyte cultures from three donors to infection by P. falciparum sporozoites. Here, we show that EEFs can be detected and isolated from in vitro infected cultures of the HC-04 cell line and primary human hepatocytes. We confirmed the presence of developing parasites in sorted live human hepatocytes and characterized their morphology by fluorescence microscopy. Finally, we validated the practical applications of our approach by re-examining the importance of host ligand CD81 for hepatocyte infection by P. falciparum sporozoites in vitro and assessment of the inhibitory activity of anti-sporozoite antibodies. This methodology provides us with the tools to study both, the basic biology of the P. falciparum liver stage and the effects of host-derived factors on the development of P. falciparum EEFs.